A Comparative Analysis of Cryptorchidism Occurrence across Sheep Varieties - Awakash Mishra, Digvijay Singh, Prerna Mahajan (Revista Electronica de Veterinaria, 2024)
Cryptorchidism is a common reproductive condition in sheep that can have a major effect on both fertility and the overall production of the herd. The purpose of this research was to determine the thorough comparative investigation of the prevalence incidence of cryptorchidism and its variants in sheep breeds. Data about the horn pattern and cryptorchidism of sheep breeds such as Hassan, Bellary, Kenguri and Mandya were gathered from shepherds’ herds in the respective habitat tracts of those sheep breeds. Hassan and Mandya sheep were used in autopsy research and ultrasound scanning to determine the percentage of cryptorchid testes retained in the gastrointestinal, inguinal and ventral areas. In sheep from Bonpala and Hassan, bilateral cryptorchidism was greater. There was a discernible deficiency in the Bonpala and Hassan breeds as evidenced by the increased retention of cryptorchid testes in the abdominal region as opposed to the femoral and subcutaneous regions. This comparative investigation sheds light on the complex nature of sheep cryptorchidism. The development of focused breeding methods and management techniques aimed to reduce the occurrence of this reproductive condition and improve the general health and productivity of sheep populations depends on the comprehension of breed-specific characteristics and environmental factors.